Crossed testicular ectopia - Sarah Magdy Abdelmohsen; Mohamed Abdelkader Osman; Mohammed Hamada Takrouney; Osama Abdelazim; Mohamed Fathy; Hussein Ali Mostafa (Elsevier, 2018)
Background: Crossed testicular ectopia (CTE) is one of the rare incidental findings during surgical intervention for an inguinal hernia or cryptorchidism, more than 100 cases have been reported in published studies. Methodology: We collected 7 cases of CTE operated during the period from September 2016 to January 2018 at 4 different university hospitals in Egypt, with the age range from (25 days-3 years); mean age at presentation was 1.6 year. Clinical presentation, intraoperative findings, operative technique and follow-up duration of 3 months up to 2 years were assessed. Results: Six cases were born full term, and one case was preterm. Four cases born as 1st offspring while 3 cases born as a 2nd offspring.Three cases associated with Persistent Müllerian duct syndrome (PMDS) (type 2), one case associated with penoscrotal hypospadias (type 3), one case associated with both (PMDS) and penoscrotal hypospadias (type 3), one case associated with congenital inguinal hernia only (type 1), and one case was not associated with a hernia or any associated anomalies.Three cases discovered accidentally during laparoscopic exploration for undescended testes, two of them had a common vas deferens or union cord.Surgery was offered to all patients, five cases were operated by Ombredanne's technique; one case was operated by laparoscopic intraperitoneal transposition approach and the last case had one testis atrophied which may be attributed to the ischemic effect of obstructed hernia but the other associated testis was normally vascularized. All testes except one atrophied fixed at ipsilateral subdartos pouch. Conclusion: CTE may be present in cases of cryptorchidism with or without an associated congenital hernia and may be discovered incidentally during diagnostic laparoscopy for cryptorchidism. It should be suspected in any case of abscent testis with congenital hernia in the same side. Karyotyping is recommended for cases of CTE with PMDS. We cannot find an evidence for relationship between prematurity and CTE as most of our cases were full term. Keywords: Transverse testicular ectopia (TTE), Persistent Müllerian duct syndrome (PMDS), Crossed testicular ectopia (CTE), Common cord, Orchiopexy